The Effectiveness Of Addition Mycorrhizae And Fertilizer Composition On The Spinach’s Growth (Amaranthus sp) - ambar susanti; Andreas Abdul Aziz; Anton Muhibuddin (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2021)
The production of organic spinach hasn’t been able to keep up with market demand, it is necessary to produce quantity and organic spinach. The research was carried out in the laboratory and greenhouse of the Agriculture Faculty, KH.A. Wahab Hasbullah University in February - May 2021. The purpose of this study was to aims to determine the effectiveness of giving mycorrhizae to spinach plants given various organic fertilizer compositions with the decomposer Trichoderma sp. The research design used was a completely randomized design, with five treatments and five replications. The treatments are; M0 (8 grams of mycorrhizae with 0% organic fertilizer as negative control), M1 (8 grams of mycorrhizae with 25% organic fertilizer), M2 (8 grams of mycorrhizae with 50% organic fertilizer), M3 (8 grams of mycorrhizae with fertilizer organic 75%), M4 (8 gr mycorrhizal with 5 grams of NPK fertilizer as positive control). The results are M2 treatment showed good growth in plant height (18.26 cm), the number of leaves (8.40 leaves), plant wet weight (3.65 gr), and root length (13.69 cm). Mycorrhizal spinach plants are effective in absorbing nutrients available in organic fertilizers 50% of the composition of the growing media, but less effective at 25%,75%, and NPK Mutiara 16:16:16 fertilizer. Organic fertilizers with local Trichoderma sp isolate decomposer are able to provide nutrients needed by spinach plants for their growth. The application of organic fertilizers with a composition of 50% to plants given mycorrhizae is possible to suppress the use of inorganic fertilizers.